Design of a comparative effectiveness randomized controlled trial testing a faith-based Diabetes Prevention Program (WORD DPP) vs. a Pacific culturally adapted Diabetes Prevention Program (PILI DPP) for Marshallese in the United States. Issue 19 (May 2018) - McElfish, Pearl Anna; Long, Christopher R.; Kaholokula, Joseph Keawe'aimoku; Aitaoto, Nia; Bursac, Zoran; Capelle, Lucy; Laelan, Melisa; Bing, Williamina Ioanna; Riklon, Sheldon; Rowland, Brett; Ayers, Britni L.; Wilmoth, Ralph O.; et al.
Abstract: Background: Pacific Islander populations, including Marshallese, face a disproportionately high burden of health disparities relative to the general population. Objectives: A community-based participatory research (CBPR) approach was utilized to engage Marshallese participants in a comparative effectiveness trial testing 2 Diabetes Prevention Program (DPP) interventions designed to reduce participant's weight, lower HbA1c, encourage healthy eating, and increase physical activity. Design: To compare the effectiveness of the faith-based (WORD) DPP to the culturally adapted (Pacific Culturally Adapted Diabetes Prevention Program [PILI]) DPP, a clustered randomized controlled trial (RCT) with 384 Marshallese participants will be implemented in 32 churches located in Arkansas, Kansas, Missouri, and Oklahoma. Churches will be randomly assigned to WORD DPP arm or to PILI DPP arm. Methods: WORD DPP focuses on connecting faith and health to attain a healthy weight, eat healthy, and be more physically active. In contrast, PILI DPP is a family and community focused DPP curriculum specifically adapted for implementation in Pacific Islander communities. PILI focuses on engaging social support networks to maintain a healthy weight, eat healthy, and be more physically active. All participants are assessed at baseline, immediate post intervention, and 12 months post intervention. Summary: Both interventions aim to cause weight loss through improving physical activity and healthy eating, with the goal of preventing the development of T2D. The clustered RCT will determine which intervention is most effective with the Marshallese population. The utilization of a CBPR approach that involves local stakeholders and engages faith-based institutions in Marshallese communities will increase the potential for success and sustainability. This study is registered at clinicaltrials.gov (NCT03270436).